p97 regulates GluA1 homomeric AMPA receptor formation and plasma membrane expression - Yuan Ge (Nature Portfolio, 2019)
AMPA receptors mediate excitatory synaptic transmission and are involved in synaptic plasticity. The authors show that p97 interacts with the GluA1 subunit of AMPA receptors, promotes the formation of GluA1 homomeric AMPA receptors, and regulates AMPA receptor trafficking during synaptic plasticity.